Understanding the decline of mean systolic blood pressure in Japan: an analysis of pooled data from the National Nutrition Survey, 1986-2002 - Nayu Ikeda; Emmanuela Gakidou; Toshihiko Hasegawa; Christopher JL Murray (Bulletin of the World Health Organization, 2008)
OBJECTIVE: To assess the relationships between the observed drop in mean systolic blood pressure (SBP) in Japan in 1986-2002 and the use of antihypertensive treatment and lifestyle factors. METHODS: A nationally representative sample of 90 554 men and 101 903 women aged 20 years and over was obtained from pooled data of annual cross-sectional surveys in Japan during 1986-2002. Using two-stage least squares with an instrumental variable, we examined the association between SBP and antihypertensive medication and lifestyle factors, including body mass index (BMI), physical activity, alcohol consumption, cigarette smoking and dietary salt intake. In the surveys, regular exercise was defined as exercise for more than 30 minutes at a time more than twice a week for over 1 year. Current smoking was defined as either daily or occasional cigarette use. Current drinking was defined as an intake of more than one standard cup of Japanese sake, one large bottle of regular beer, or one double measure of whisky at a time more than three times a week. Changes in mean predicted SBP in each sex and age group between 1986 and 2002 were decomposed into the respective contributions of these explanatory variables. FINDINGS: Age-specific means of predicted SBP declined during this period by 1.8 (95% confidence interval, CI: 1.2-2.5) to 3.0 (95% CI: 2.4-3.6) mmHg in men and 3.7 (95% CI: 3.4-4.1) to 5.1 (95% CI: 4.5-5.7) mmHg in women. These reductions were partly explained by the increased use of medications across all sex and age groups and decreased mean BMI in women in their 30s and 40s. The contributions of treatment effects increased with age. Elevated mean BMI in men and elderly women offset part of the decline of their mean SBP. CONCLUSION: Declining mean SBP in Japan between 1986 and 2002 was partly attributable to the increased use of antihypertensive medications, especially in the older population, and lowered mean BMI in young women. However, a substantial part of the decline was left unexplained and needs to be investigated further. A still greater decline in SBP would be expected through improvements in body weight management, salt and alcohol intake, and treatment and control of hypertension.